Cognitive function and its relationship to other psychosocial factors in lymphoma survivors. - Krolak, Dorothy; Collins, Barbara; Weiss, Lorelle; Harris, Cheryl; Van der Jagt, Richard (Supportive Care in Cancer, 2017)
Purpose: The purpose of this study was to estimate the prevalence of cognitive disturbance in lymphoma survivors and to explore relationships between cognitive function and other psychosocial factors.Methods: A package of standardized questionnaires was sent to 622 lymphoma patients treated at the Ottawa Hospital in the preceding 5 years. Patients with central nervous system involvement were excluded. The questionnaires addressed cognitive function, pain, insomnia, fatigue, and mood. Of the patients in the sampling frame, 54 % responded to the survey and 42 % met inclusion/exclusion criteria. Sixteen percent (99/622) agreed to undergo computerized neuropsychological testing with CNS vital signs (CNSVS). Scores on the objective and subjective cognitive measures were compared to those of a healthy female control group from a previous study.Results: The lymphoma group scored significantly lower than the controls on a cognitive rating scale (p = .018) and on CNSVS (p = .035). The difference on the CNSVS was primarily due to poorer attention and executive function scores in the lymphoma patients. The patients also had a higher frequency of impairment on both the objective (p = .009) and subjective (p < .001) cognitive measures. Among the lymphoma survivors, fatigue and anxiety were related to subjective cognitive disturbance (p < .001 for both), whereas pain was the only psychosocial measure associated with objective cognitive performance (p < .001).Conclusions: These results suggest that cognitive disturbance may be a significant survivorship issue for lymphoma patients and should be more thoroughly investigated in this population.